ENHANCHING THE INTERNAL QUALITY AUDIT (AMI) AT UNIVERSITAS NEGERI MAKASSAR THROUGH THE CIPP EVALUATION MODEL: A QUALITATIVE ASSESSMENT - Irmawati; Syam, Sriwidayani; Tompong, By Tri Agung Nusantara Kr. J. (Irfani, 2025)
This study examines the implementation of the 2024 Internal Quality Audit (AMI) at the State University of Makassar (UNM) using the Context, Input, Process, Product (CIPP) evaluation model to assess the effectiveness of the implementation of quality assurance in eleven faculties. Using a qualitative descriptive method, data was collected from audit reports, Management Review Meeting (RTM) results, and institutional documents. The analysis shows that all faculties have implemented the PPEPP cycle consistently, although the depth and integration of practice varies. Faculties such as FMIPA and FIKK demonstrate superior practices, including infrastructure support and human resource readiness, while other faculties such as FIP face challenges in strategic documentation and integration of the MBKM curriculum. This study identifies a number of aspects that need to be improved, such as stakeholder engagement, the use of tracer studies, and more systematic follow-up to audit recommendations. This study recommends the digitization of the audit system, periodic auditor training, and the formal involvement of alumni and graduate users in the quality assurance process. The findings of the study confirm the relevance of the CIPP model as an effective evaluation framework in assessing and improving the internal audit function in universities. By providing a comprehensive understanding of audit performance and institutional gaps, this research contributes to the development of sustainable quality assurance practices at UNM and similar institutions